2005
DOI: 10.1111/j.1365-2648.2004.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

A theory of maternal engagement with public health nurses and family visitors

Abstract: Public health nurses working with families at risk need to identify client fears and perceptions related to home visiting, and to explain the role of public health nurses and family visitors to all family members. Given the importance that mothers place on the development of an interpersonal relationship, it is important for home visitors continually to assess the quality of their relationships with clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 22 publications
7
110
0
2
Order By: Relevance
“…A review of the published and grey literature indicated that while there was a heavy focus on program evaluation, the majority of evaluation reports do not include an investigation of clients' perspectives of intensive home visiting programs. There are five studies that have specifically investigated parents' perspectives of intensive nurse home visiting programs: two of these studies are from the United Kingdom (McIntosh & Shute, 2006;Kirkpatrick et al, 2007), two from Canada (Jack et al, 2005;Heaman et al, 2005) and one from the United States of America (DeMay, 2003). Five major themes were identified during the review of these studies, they included: negative preconceptions, trusting relationships, support, empowerment, and change.…”
Section: Program Evaluationmentioning
confidence: 99%
“…A review of the published and grey literature indicated that while there was a heavy focus on program evaluation, the majority of evaluation reports do not include an investigation of clients' perspectives of intensive home visiting programs. There are five studies that have specifically investigated parents' perspectives of intensive nurse home visiting programs: two of these studies are from the United Kingdom (McIntosh & Shute, 2006;Kirkpatrick et al, 2007), two from Canada (Jack et al, 2005;Heaman et al, 2005) and one from the United States of America (DeMay, 2003). Five major themes were identified during the review of these studies, they included: negative preconceptions, trusting relationships, support, empowerment, and change.…”
Section: Program Evaluationmentioning
confidence: 99%
“…17 In addition, for research purposes, CHWs are employed to collect data from the communities they serve 15,18,22,34 or are identified as key informants regarding those communities. 11,18,19,32,33,35 Community knowledge Community knowledge is essential to the roles of CHWs. First, community origin or in-depth knowledge of the community is necessary to build trust, respect and mutual understanding between the CHWs and the communities they serve.…”
Section: Education and Trainingmentioning
confidence: 99%
“…In urban settings, where communities may be scattered in different parts of the city, community origin or knowledge about community is taken into account by the organization deploying CHWs without the communities necessarily being consulted. 18,19 Aside from organizational recruitment, there are post-secondary educational programs intended to train and to lead to employment of Aboriginal CHWs. 20 …”
Section: Recruitmentmentioning
confidence: 99%
“…Ao assumir o risco de engajar-se em determinado comportamento participativo e em uma relação com o profissional de saúde a família utiliza estratégias para proteger sua integridade e limitar sua vulnerabilidade, que envolvem o vencer os próprios medos, tentando mostrar-se a altura do profissional e protegendo seu self; construir confiança, abrindo-se, testando e buscando confidencia; e o buscar mutualidade, compartilhando experiências e buscando reforçar suas habilidades de cuidado familiar (79) .…”
Section: Capítulounclassified